Ask a question
0 0

solve the equation log3 (3x-6) = log3 (2x+1)

solve the equation log3 (3x-6) = log3 (2x+1)
Tutors, please sign in to answer this question.

3 Answers

In this problem, you shouldn't be confused by the log3 since we know that when the log3 a = log3 b, then very simply a must be equal to b.  In this problem a=3x-6 and b=2x+1
So:  3x-6=2x+1
Hope this helps!
George T.
Hi Heather;
log3 (3x-6) = log3 (2x+1)
Before I answer this, I was like to briefly review logarithms.
Let's just say that...
log3 (3x-6) = 5
I randomly selected the number 5.
This would resolve as...
Do you see how the base 3 moved to the other side of the = sign and became a 3, whereas the 5 rose to exponential status of 5?
I love the way Megan described the components as base, exponent and "answer".  If she does not mind, I intend to use it in future answers.
In the equation you provided, the base of 3 appears on both sides of the equation.  Henceforth...
log3 (3x-6) = log3 (2x+1)
we can cancel these.
Let's add 6 to both sides as we proceed to isolate x...
Let's subtract 2x from both sides...
Let's verify...
(3x-6)  ???   (2x+1)
[3(7)-6] ??? [2(7)+1]
21-6  ???  14+1
All Good!
Hey Heather!
log39=2   -->example
3 is the base, 2 is the exponent and 9 is what I call the answer. You can rewrite this expression as 32=9 so you can see that. In the expression you have both of your logs have the same base of 3 and since they are set equal to each other tell you that they must have the same exponent. Therefore the answers must be equal so you can just set 3x-6=2x+1 and solve for x. 
In this similar problem:
2x-2 = x+1    -->set answers equal to eachother
x-2=1            --> solve for x
Good Luck!